Um estudo sobre as leis dos cossenos, senos, tangentes e cotangentes explorando os pacotes gráficos do LATEX: ‘animate’, ‘tikz’, ‘tkz-base’ e ‘tkz-euclide’ - Lima, Marconi Ferreira (2025)
In this work we discuss some results of trigonometry, more precisely, we study the laws of cosines, sines, tangents and cotangents exploring the graphical packages of LATEX: ‘animate’, ‘tikz’, ‘tkz-base’ and ‘tkz-euclide’. We present geometric proofs and “proof without words” of these results, as well as some curious consequences. Finally, we explore some generalizations of these results in the context of spherical geometry, and we provide some of the LATEX element sets needed to produce most of the figures presented here.